الأدب النّسوي وإشكاليّة المصطلح (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
إنَّ النّصوصَ الأدبيَّة التي أبدعتها المرأة جاءت مشحونةً بالرّفض والاحتجاج والثورة على عالمٍ يمجّد الذّكورة ويقدّسها، معبّرة في الوقت ذاته عن توقها الشّديد إلى تحقيق حلم المساواة مع نصفها الآخر (الرّجل). إلاَّ أنَّ إمكانيّة دراسة أدب المرأة في مجال النّقد، وإمكانيّة تأصيل مصطلح "الأدب النّسوي" أو نفيه أثار الكثير من الجدل والنّقاش بين القرّاء والأدباء والنّقاد. من هنا جاء هذا البحث ليستقرئ المقاربات النّقديّة، ويرصد الآراء والمواقف المختلفة التي دارت حول هذا الموضوع مؤكّداً في النهاية ضرورة تأصيل مصطلح " الأدب النّسويّ" نقديّاً، وذلك لفصل خطاب المرأة عن كينونتها الأنثويّة ولتحرير وعيها، ولفسح المجال لوجهة النّظر المختلفة بعيداً عن المصادرة والتهّميش والتّقويم. فاختلاف خطاب المرأة عن خطاب الرّجل اختلاف طبيعي نظراً لاختلاف التّجربة والظروف والثقافة والتكوين.   Literary texts created by women come charged with refusal, protest, and rebel against a world that glorifies and sanctifies masculinity par excellence, revealing, at the same time, women’s great eagerness to realize the dream of equality with their second half – the man. Yet, the possibility of studying woman literature in the field of criticism, and the possibility of canonizing the term ‘Feminist Literature’ or negating it have aroused a lot of debate and controversy among readers, writers, and critics. Hence, this research comes to investigate the critical approaches and to survey the different opinions and attitudes that have been circulating around this issue, asserting the urgency of canonizing the term ‘Feminist Literature’ critically. Consequently, this will separate the woman’s discourse from her female essence and liberate her conscious. Moreover, it will open the way for a diverse point of view far from any marginalization. The difference, then, between the woman’s discourse and the man’s discourse is a natural one considering the differences of the experience, circumstances, culture, and physique.